Quelle pauvreté réduire ? Le problème de la réduction utilitariste de la richesse - Alain Girard; Bernard Schéou (Études Caribéennes)
By adopting the Millennium Development Goals (MDGs) in the United Nations in 2000, the international community has made poverty reduction a top priority on the global political agenda. In doing this, the international community has put poverty reduction in the media spotlight, which has also made it more difficult to challenge. Yet who would decently oppose the reduction of global poverty?If we want to target the poor in policy implementation, it is first necessary to be able to recognize them. But these people are defined by international institutions based on a universal poverty threshold established at less than $1 - $2 per day. Poverty depends on a multitude of geographic, cultural, sociological, psychological and other criteria. As such, it cannot be reduced merely to a question of daily monetary wealth.This reductionist approach to poverty leads to adopt categorizations which are sometimes arbitrary and stigmatizing because they label people who do not necessarily consider themselves poverty-stricken. This can result in policy which targets the wrong people, and in some cases contributes to a transition from poverty to misery.In this paper we propose a deconstruction of the utilitarian approach to poverty and wealth on which most “poverty reduction” policies are based. This deconstruction allows us not only to emphasize the diversity of types of poverty, but also to reinforce the objective of "reducing poverty" within power relations in regards to the significance of poverty and the concepts of wealth that can legitimize that power.